Influence of Rubber Content on Mechanical, Thermal, and Morphological Behavior of Natural Rubber Toughened Poly(Lactic Acid)-Multiwalled Carbon Nanotube Nanocomposites - Mohd Shaiful Zaidi, Mat Desa; Azman, Hassan; Agus, Arsad; Reza, Arjmandi; Nor Nisa Balqis, Mohammad (Wiley, 2016)
The effects of natural rubber (NR) on the mechanical, thermal, and morphological properties of multiwalled carbon nanotube (CNT) reinforced poly(lactic acid) (PLA) nanocomposites prepared by melt blending were investigated. A PLA/NR blend and PLA/CNT nanocomposites were also produced for comparison. The tensile strength and Young's modulus of PLA/CNT nanocomposites improved significantly, whereas the impact strength decreased compared to neat PLA. The incorporation of NR into PLA/CNT significantly improved the impact strength and elongation at break of the nanocomposites, which showed approximately 200% and 850% increases at 20 wt % NR, respectively. However, the tensile strength and Young's modulus of PLA/NR/CNT nanocomposites decreased compared to PLA/CNT nanocomposites. The morphology analysis showed the homogeneous dispersion of NR particles in PLA/NR/CNT nanocomposites, while CNTs preferentially reside in the NR phase rather than the PLA matrix. In addition, the incorporation of NR into PLA/CNT lowered the thermal stability and glass-transition temperature of the nanocomposites.